Psychological Well-Being and Academic Performance: A Study of Educational Counseling Programs in Indonesian High Schools - Utari Hadrawii; Miranda; Agus Pratama (Generasi Sains Indonesia, 2025)
Psychological well-being plays a pivotal role in shaping students' academic performance, yet its impact within Indonesian high schools remains underexplored. This study aims to investigate the relationship between psychological well-being and academic success, with a focus on the effectiveness of counseling programs. A mixed-methods approach was employed, involving quantitative assessments of academic performance and psychological well-being, alongside qualitative interviews with students, counselors, and teachers. The results revealed a significant positive relationship between psychological well-being and academic performance, with self-acceptance and personal growth being the most influential dimensions. Counseling programs were found to significantly enhance students’ emotional regulation, stress management, and interpersonal skills, which in turn positively impacted their academic outcomes. However, challenges related to the accessibility and duration of counseling sessions were noted, suggesting that increased resources and better integration of these services within the school system are needed. This study highlights the crucial role of psychological support in improving both students' mental health and academic performance. It contributes to the broader understanding of how school-based counseling programs can be optimized to support students’ overall development. Future research should focus on the long-term effects of counseling programs and explore the most effective interventions to support students' psychological well-being in the academic context.